Development of Kodály Hand Sign Educational Tools using Multi-Layer Perceptron - Young Bae Yun; Young Man Kwon; Myung Jae Lim; Jeong Jun Park; Dong Kun Chung (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hand signs have been recognized to be useful in enhancing the effectiveness of music learning in music education. In particular, Kodály hand signs based on the Kodály teaching method are widely used around the world because their effectiveness has been recognized. The purpose of this study is to implement a hand sign recognition system using a neural network and to present a method that can systematically learn hand signs. Device-based systems were considered for portability, activity, and economy. In addition, the introduction of additional filtering to the neural network input was proposed to improve portability and recognition rate to small devices.